Older Adults Encode Task-Irrelevant Stimuli, but Can This Side-Effect be Useful to Them? - Gaál, Zsófia Anna; Nagy, Boglárka; File, Domonkos; Czigler, István (Frontiers in Human Neuroscience, 2020)
We studied whether, due to deteriorating inhibitory functions, older people are more likely to process irrelevant stimuli; and if so, could they later use this information better than young adults. In the study phase of our experiment a Posner-type gaze-cued version of a Simon task was performed in which we presented task-irrelevant cues, where faces or patches with either left- or right-looking dots for the pupil of the eye preceded the task to press a button congruent or incongruent with the presentation side of the target stimulus. In the follow-up test phase, participants completed an unexpected facial recognition test. In the study phase not only a decreased P1, but also an increased N170 amplitude of the event-related potentials (ERPs) was found in older, compared to younger adults, and also for faces compared to patches. Even though in the test phase both age-groups could recognise the faces better than statistically by chance, neither the older nor the younger participants could discriminate them effectively. The late positive component (LPC) – the ERP correlate of the old/new effect, being the higher amplitude for the earlier presented stimuli when compared with the unseen stimuli during the recognition test – was not evolved in the older group, while a reversed old/new effect was seen in younger participants: higher amplitude was found in New-Right and Old-Wrong conditions (for faces they did not recognise independent of seeing them before) compared to Old-Right and New-Wrong conditions (for faces they thought they recognised from the study phase). In conclusion, although older adults showed enhanced processing of task-irrelevant stimuli compared to younger adults, as indicated by the N170 amplitude, however, they were not able to utilize this information in a later task, as was suggested by the recognition rate and LPC amplitude results.